Breaking bad news to antenatal patients with strategies to lessen the pain: a qualitative study - José Atienza-Carrasco; Manuel Linares-Abad; María Padilla-Ruiz; Isabel María Morales-Gil (BMC, 2018)
Abstract Background To consider the thoughts and actions of healthcare personnel in situations when an adverse prenatal diagnosis must be communicated, including appropriate strategies and skills to respond to information needs and to manage the emotional responses of patients. Methods Descriptive qualitative study using non-participant observation and semi-structured interviews to analyse the discourses of physicians, midwives, nurses and nursing assistants who provide healthcare to obstetric patients. Results There may be barriers to effective communication between healthcare personnel and patients, depending on the characteristics of the persons involved, the organisation of healthcare, biotechnological progress and cultural factors. Conclusions The human quality of healthcare has deteriorated due to excessive workloads and to the growing role played by technology. In order to improve communication, more attention should be paid to human and spiritual dimensions, prioritising empathy, authenticity and non-judgmental listening. An appropriate model of clinical relationship should be based on shared decision making, clarifying the functions of the multidisciplinary team to alleviate a mother's suffering when a pregnancy is interrupted. To do so, protocols should be implemented to ensure the provision of comprehensive care, not only addressing biological issues but also providing psychosocial attention. Finally, training should be provided to healthcare staff to enhance their social skills and cultural competence. This study identifies potential improvements in the interventions made by healthcare personnel and in the organisation of the institution, concerning the attention provided to pregnant women when an adverse prenatal diagnosis must be communicated.